Social information (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2014)
Based on Erving Goffman’s work, the article aims to discuss a definition of information centered on the type conveyed by individuals in a multimodal way, encompassing language and body in situations of co-presence, where face-to-face interaction occurs, and influencing inter-subjective formation of the self. Six types of information are highlighted: material information, expressive information, ritualized information, meta-information, strategic information, and information displays. It is argued that the construction of this empirical object tends to dissolve the tension among material, cognitive and pragmatic aspects, constituting an example of the necessary integration among them. Some vulnerable characteristics of the theory are critically mentioned and it is suggested that the concept of information displays could provide a platform to approach the question of the interaction order in its relations with the institutional and social orders, and consequently, to reassess the scope of the notion of social information analyzed.Keywords: Goffman. Social information. Social interaction.Link para o texto completo (PDF)http://periodicos.puc-campinas.edu.br/seer/index.php/transinfo/article/view/1955/1751